PELAKSANAAN DOKUMENTASI ASUHAN KEBIDANAN TERHADAP PERLINDUNGAN HUKUM PASIEN PADA BIDAN PRAKTIK MANDIRI (Studi di Kabupaten Cilacap) - DEWI PUSPITASARI (Jurnal Idea Hukum, 2019)
There are still many Independent Practical Midwives in Cilacap District who have not systematically carried out midwifery documentation even though it is needed to know the progress in patient care. This is because midwives have obligations as stipulated in the Regulation of the Minister of Health No. 28 of 2017 on Article 28, namely that midwives have the obligation to systematically record documentation. Registration of midwifery care must be recorded in accordance with midwifery service standards in accordance with Kepmenkes No. 369 of 2007 concerning Midwife Professional Standards. Therefore, this study examines the implementation of midwifery care documentation on BPM and patient legal protection at BPM in Cilacap Regency.This research uses sociological juridical approach, with analytic descriptive type, and using primary data through interview and docuent study with Head of Health Service and Community Resource of Cilacap District Health Office, Head of IBI Branch of Cilacap District, each Head of Branch of Cilacap District, Practice of Midwife in Cilacap District.The results showed that the implementation of documentation on BPM was not in accordance with the Decree of the Ministry of Health 369 of 2007 because there were still midwives using the narrative model recording technique to record everything that was examined by the midwife without mentioning the patient's progress notes. Constraints to the implementation of midwifery care documentation on patient legal protection at BPM in Cilacap Regency are documentation of non-systematic documentation due to lack of awareness of midwives in carrying out systematic documentation, and monev conducted not periodically only when SIPB is extended. So what needs to be considered to solve the problem is that socialization continues to be improved regarding documentation at the BPM according to the midwife's professional standards, periodically monitoring the BPM, and giving strict sanctions to the violating midwife